2012
DOI: 10.3892/or.2012.1632
|View full text |Cite
|
Sign up to set email alerts
|

Generation of reactive oxygen species mediates butein-induced apoptosis in neuroblastoma cells

Abstract: Flavonoids exhibit chemopreventive and chemotherapeutic effects. Butein, a bioactive flavonoid isolated from numerous native plants, has been shown to induce apoptosis in human cancer cells. In the current study, the molecular mechanisms of butein action on cell proliferation and apoptosis of neuroblastoma cells were evaluated. Treatment with butein decreased the viability of Neuro-2A neuroblastoma cells in a dose- and time-dependent manner. The dose-dependent nature of butein-induced apoptosis was characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 23 publications
1
26
0
1
Order By: Relevance
“…The A549 cells were seeded in 24-well plates at a density of 2x10 4 /ml and were treated with 0, 25, 50, 100, 200 and 300 µM naringenin for 24 and 48 h. Following the treatment, the cells were incubated with fresh medium containing 5.0 g/l MTT, and incubated at 37˚C for an additional 2 h. After washing with PBS, the sediments were dissolved in 1 ml isopropanol and the absorbance at 563 nm was determined. The relative viability rate was determined based on the absorbance at 563 nm of each sediment compared with vehicle-treated groups.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The A549 cells were seeded in 24-well plates at a density of 2x10 4 /ml and were treated with 0, 25, 50, 100, 200 and 300 µM naringenin for 24 and 48 h. Following the treatment, the cells were incubated with fresh medium containing 5.0 g/l MTT, and incubated at 37˚C for an additional 2 h. After washing with PBS, the sediments were dissolved in 1 ml isopropanol and the absorbance at 563 nm was determined. The relative viability rate was determined based on the absorbance at 563 nm of each sediment compared with vehicle-treated groups.…”
Section: Methodsmentioning
confidence: 99%
“…For example, butein inhibits the migration and invasion of bladder cancer cells by reducing the expression of extracellular signal-regulated kinase 1/2 and its activities (3). In addition, butein has been found to elevate reactive oxygen species (ROS) levels and trigger apoptosis in neuroblastoma (4) and breast cancer cells (5,6). Moreover, shikonin induces apoptosis in osteosarcoma cells via the generation of ROS (7).…”
Section: Introductionmentioning
confidence: 99%
“…Butein has been shown to increase ROS levels in neuroblastoma cells and breast cancer cells [31,36] and also functions as antioxidant for liver stellate cells and keratinocytes [21,37]. OA chondrocytes treated with Butein showed no increase in ROS levels as measured by DCFDA (Fig.…”
Section: Butein Activated Autophagy Via Ampk/tsc2/ulk1/mtor Pathway Imentioning
confidence: 99%
“…There are reports that have shown that Butein reduces cell viability and enhances apoptosis in multiple cancer cells including ovarian cancer cells [30] cervical cancer cells [23], neuroblastoma [31] and T-cell lymphoma [32]. In order to study the effects of Butein on the viability of OA chondrocytes, OA chondrocytes were treated with different concentrations of Butein [0.6 μg/ml -10 μg/ml (or 2.25 μM -36 μM)] for 24 hr or with 10 μg/ml Butein for up to 72 hr and the viability was analyzed by MTT assay.…”
Section: Butein Did Not Affect the Viability Of Oa Chondrocytes In Vitromentioning
confidence: 99%
“…Simultaneously it decreases the Bcl-2/Bax ratio. 9 The ultimate result is marked accentuation of intratumoral apoptosis.…”
Section: 1mentioning
confidence: 99%